2012
DOI: 10.1016/j.schres.2012.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state networks in adolescents with 22q11.2 deletion syndrome: Associations with prodromal symptoms and executive functions

Abstract: Atypical functional connectivity in the maturing brains of 22q11.2 deletion syndrome (22q11DS) may contribute to the expression of early psychotic symptoms commonly reported by these youths. This study's objective was to examine functional connectivity in cerebral networks at rest (Resting-State Networks; RSNs) and their relationship to symptomatic and neuropsychological characteristics putting them at very high risk factor for developing psychosis. Twenty-seven adolescents with 22q11DS and 33 typically develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 49 publications
7
60
0
Order By: Relevance
“…Our data largely support prior observations using other modalities (Debbané et al, 2012, Ottet et al, 2013b, Padula et al, 2015, Scariati et al, 2016, Simon et al, 2005). For example, Ottet et al reported significant reductions in occipito-occipital and limbic connectivity in 22q11DS using DTI tractography in 30 individuals with 22q11DS and 30 typically developing controls, as well as a 10% reduction in the total number of fibers (Ottet et al, 2013a).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data largely support prior observations using other modalities (Debbané et al, 2012, Ottet et al, 2013b, Padula et al, 2015, Scariati et al, 2016, Simon et al, 2005). For example, Ottet et al reported significant reductions in occipito-occipital and limbic connectivity in 22q11DS using DTI tractography in 30 individuals with 22q11DS and 30 typically developing controls, as well as a 10% reduction in the total number of fibers (Ottet et al, 2013a).…”
Section: Discussionsupporting
confidence: 90%
“…Ottet et al later expanded these analysis using graph theoretical models in a sample of 46 participants with 22q11DS and 48 matched controls, identifying significantly increased global path lengths and reduced global efficiency (Ottet et al, 2013b). Using resting state fMRI, Debbané et al reported that individuals with 22q11DS had weaker connectivity in visuospatial, frontotemporal, and sensorimotor networks, as well as within the default mode network (Debbané et al, 2012). Alterations to the dorsal stream have long been postulated to explain the observed deficits in visuospatial and mathematical ability in 22q11DS, and several prior structural studies have identified reduced parieto-occipital volumes in people carrying the deletion (Eliez et al, 2000, Jalbrzikowski et al, 2013, Kates et al, 2001, Schmitt et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Executive function, required for problem solving and task flexibility, is perturbed in all disorders of cortical circuit development (Kenworthy et al, 2009; Montojo et al, 2014; van Os and Kapur, 2009). This apparent divergence of association cortical function in 22q11DS patients is further supported by analysis of resting state network activity (Debbane et al, 2012). Magnetic resonance spectroscopy studies suggest that these changes may reflect disruptions of synaptic mechanisms, as is the case in ASD, ADHD and SCZ (Stone, 2009; Stone et al, 2009).…”
Section: Parallel Cortical Pathology In 22q11dsmentioning
confidence: 76%
“…These studies report diminished coherence of activity measured across brain circuits, indicative of weaker connectivity in individuals born preterm from infancy1112 through adulthood1314. Given the robust linkage between child neurological disorders and atypical large-scale neural connectivity1516 (see also refs 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37), theory has evolved that neurodevelopmental impairment following preterm birth may stem from alterations in neural connectivity38, and recent evidence provides nascent support for this claim1039.…”
mentioning
confidence: 99%